2022
DOI: 10.1155/2022/5459779
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Value of Multislice Spiral CT in Differential Diagnosis of Thick‐Wall Gallbladder Carcinoma and Chronic Cholecystitis

Abstract: To summarize the value of multislice spiral CT (MSCT) in the differential diagnosis of thick-wall gallbladder carcinoma (TWGC) and chronic cholecystitis (CC), the clinical data of 36 patients with TWGC and 60 patients with chronic cholecystitis who were treated in our hospital from January 2017 to May 2021 were retrospectively analyzed, and the CT image features and diagnostic accuracy of the patients were summarized. Compared with the CC group, the proportions of disruption of gallbladder mucosa line, blurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Common CT imaging findings for GBCa include GB wall thickening, evidence of an isolated hypodense intraluminal mass, GB wall calcification, and porcelain GB. CT imaging is also especially helpful in identifying infiltration of surrounding organs, LN involvement, peritoneal nodules, and distant metastasis [18,19]. MRI of the abdomen can also be used to diagnose GBCa, which is seen as an irregular, hypointense lesion on T1-weighted images and hyperintense lesion on T2-weighted images.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Common CT imaging findings for GBCa include GB wall thickening, evidence of an isolated hypodense intraluminal mass, GB wall calcification, and porcelain GB. CT imaging is also especially helpful in identifying infiltration of surrounding organs, LN involvement, peritoneal nodules, and distant metastasis [18,19]. MRI of the abdomen can also be used to diagnose GBCa, which is seen as an irregular, hypointense lesion on T1-weighted images and hyperintense lesion on T2-weighted images.…”
Section: Imagingmentioning
confidence: 99%
“…The TOPAZ-1 trial confirmed the safety and efficacy of Durvalumab plus Gem-Cis, demonstrating improved overall survival versus placebo plus chemotherapy (estimated 24-month was 24.9% vs. 10.4%). Moreover, it showed improvements in prespecified secondary end points including objective response rate up to 26.7% vs. 18 TOPAZ-1 trial was designed to address a locally advanced-unresectable or metastatic population of biliary tract cancer-among which approximately 25% represented GBca-with previously untreated disease but included patients who developed recurrent disease more than 6 months after surgery with curative intent and more than 6 months after the completion of adjuvant therapy [77].…”
Section: (Table 2)mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%